Psychopharmacological Mechanisms of Antidepressant Withdrawal: Insights From Venlafaxine - Elliot McClure (Human Psychopharmacology: Clinical and Experimental, 2026)
ABSTRACT Antidepressant discontinuation syndrome (ADS) is widely reported yet often minimized by terminology that obscures its status as a withdrawal phenomenon. Roughly one‐third of patients using a monotherapy antidepressant develop withdrawal symptoms after discontinuation, with higher rates among patients taking venlafaxine (VEN) and those treated long‐term. VEN's dual transporter pharmacodynamics, its active metabolite, and its wide interindividual pharmacokinetic variability make it a useful model for how that vulnerability arises and expresses itself clinically. Chronic exposure reshapes serotonergic and glutamatergic signaling, producing receptor‐ and circuit‐level adaptations that constitute physiological dependence without addiction liability. When the medication is reduced in dose or stopped abruptly, these adaptations destabilize and trigger transient overcorrection in cortical and sensory networks. Patients experience this withdrawal syndrome somatically as brain zaps, vestibular disruption, and heightened affective volatility. For a substantial minority, symptoms persisting for weeks impair daily functioning and coincide with elevated suicidality. Recognizing ADS as an intrinsic, predictable phase of chronic antidepressant pharmacotherapy—not an incidental complication or adverse effect—should guide informed consent, tapering practices, and future drug development. This narrative review examines ADS through pharmacological and neurobiological frameworks, using VEN to illustrate candidate mechanisms, clinical features, and risks.